The Defensive Alliance of the Bohemian Estates in 1547: Notes on the Chronology, Legal Terminology, and Logic of the Aims of the Estates - Maťa, Petr (Dějiny – teorie – kritika, 2017)
The aim of this article is to correct certain erroneous but persisting views related to the unsuccessful uprising of the Bohemian Estates in 1547. The focus is on interpretation of its two central documents: the founding document of a defensive alliance of the Bohemian Estates of February 15, which was eventually signed by almost two thousand estate signatories, and on the anonymous grievances from the second half of March 1547, which proposes certain changes to the constitution and limitation of the royal prerogative. In literature, the name of the first of these documents, ‘přátelské snešení’ (amicable compact), was mistakenly applied to the latter text. Even in most recent studies, the two documents are repeatedly interchanged, which distorts the logic of the whole undertaking. This study analyses contemporary terms used in the documents, their formal and material aspects, their legal significance, but also various precedents for such an alliance of the Estates during the reign of George of Poděbrady and the Jagiellonian kings. It thus presents a new perspective on the alliance as such, claiming that it should not be understood as a loose association of persons who support some particular, publicly declared political goals. Rather, it should be viewed as a platform created for the purpose of stimulating and legitimising a revolt of the Estates and a means of protecting its signatories, who were contractually bound to provide mutual protection. Negotiations between the king and the Estates about the existence of the alliance and its founding document thus amounted to a conflict about legality of the organised efforts of the Estates as such.